Determinants of implantable defibrillator discharges in high-risk patients with hypertrophic cardiomyopathy. Issue 9 (14th August 2007) - Woo, Anna; Monakier, Daniel; Harris, Louise; Hill, Ann; Shah, Prasad; Wigle, E Douglas; Rakowski, Harry; Rozenblyum, Evelyn; Cameron, Douglas A
Abstract : Objectives: To identify the determinants of appropriate and inappropriate implantable cardioverter-defibrillator (ICD) discharges in patients with hypertrophic cardiomyopathy (HCM). Design: Retrospective cohort study. Setting: ICD clinic at an academic hospital. Patients: 61 patients with HCM who received ICDs for the primary or secondary prevention of sudden cardiac death (SCD). Outcome measures: ( a ) Analysis of appropriate and inappropriate ICD discharges; ( b ) predictors of ICD discharges. Results: Mean (SD) age at ICD insertion was 46 (18) years (range 10–79). Follow-up time was 40 (27) months (range 7–151). Eight patients experienced an appropriate discharge, occurring 24.5 (13.6) months after ICD insertion. Appropriate ICD intervention was more common in the secondary (36%) than the primary (8%) prevention group (p = 0.02). Inappropriate ICD discharges occurred in 20 (33%) patients. Multivariate Cox regression analysis identified two significant predictors of inappropriate ICD discharges: ( a ) age <30 years at the time of ICD insertion (hazard ratio (HR) = 3.0 (95% CI 1.1 to 8.0; p = 0.03) and ( b ) history of atrial fibrillation (HR = 3.1 (95% CI 1.2 to 8.1; p = 0.02). Conclusions: ICDs are effective in the prevention of SCD in HCM. However, there is a high incidence of inappropriate ICD discharges.